2016
DOI: 10.1371/journal.ppat.1005737
|View full text |Cite
|
Sign up to set email alerts
|

Potent Allosteric Dengue Virus NS5 Polymerase Inhibitors: Mechanism of Action and Resistance Profiling

Abstract: Flaviviruses comprise major emerging pathogens such as dengue virus (DENV) or Zika virus (ZIKV). The flavivirus RNA genome is replicated by the RNA-dependent-RNA polymerase (RdRp) domain of non-structural protein 5 (NS5). This essential enzymatic activity renders the RdRp attractive for antiviral therapy. NS5 synthesizes viral RNA via a “de novo” initiation mechanism. Crystal structures of the flavivirus RdRp revealed a “closed” conformation reminiscent of a pre-initiation state, with a well ordered priming lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
156
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(164 citation statements)
references
References 51 publications
7
156
1
Order By: Relevance
“…A previous study, through fragment-based crystallography method, identified a pocket near to the active site of the DENV3 RdRp domain, termed ‘N pocket', which binds to a small-molecule that inhibits DENV3 NS5-mediated RNA initiation and elongation (Fig. 4a)25. Detailed analysis of this inhibitor-binding site revealed that the critical residues for the inhibitor binding are also conserved in ZIKV NS5, arranged in a similar structural environment (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…A previous study, through fragment-based crystallography method, identified a pocket near to the active site of the DENV3 RdRp domain, termed ‘N pocket', which binds to a small-molecule that inhibits DENV3 NS5-mediated RNA initiation and elongation (Fig. 4a)25. Detailed analysis of this inhibitor-binding site revealed that the critical residues for the inhibitor binding are also conserved in ZIKV NS5, arranged in a similar structural environment (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…These results suggest that inhibitors of viral MT activity and/or RNA synthesis can be developed to inhibit ZIKV replication. In fact, nucleoside analogues that can inhibit the polymerases of Dengue virus, West Nile virus and yellow fever virus have recently been shown to affect RNA synthesis by ZIKV NS5 (refs 5, 21, 22, 23, 24). Sofosbuvir, which is highly effective in treating hepatitis C, also has modest inhibitory activity for the replication of the ZIKV25.…”
Section: Discussionmentioning
confidence: 99%
“…Nonstructural protein 5 (NS5) is essential for the replication of the flaviviral RNA genome456. The N-terminal portion of NS5 contains a methyltransferase (MT), followed by a short linker that connects to the RNA-dependent RNA polymerase (RdRp).…”
mentioning
confidence: 99%
“…The ZIKV thumb, palm and fingers domains are also well superimposed on the equivalent domains of DENV2 and DENV3 (r.m.s.d. of 1.17 Å and 1.19 Å, respectively)612. Nevertheless, a close inspection at the priming loop revealed structural elements that differ from DENV homologues and might impact on inhibitor discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Although nucleoside polymerase inhibitors (NPIs) have achieved clinical success in the case of Hepatitis C virus infections (for example, sofosbovir), they depend on activation by host kinases and are potentially subjected to toxicity problems5. Therefore, non-NPIs have been actively sought as inhibitors of flaviviral NS5 RdRp, particularly targeting the so-called priming loop, that regulates RNA-template binding and polymerization6. Recently, several groups reported the discovery of novel RdRp inhibitors with pan-serotype activity against dengue viruses (DENV).…”
mentioning
confidence: 99%